전자빔 증발원을 이용한 물질의 증발 특성 - 정재인(J. I. Jeong); 양지훈(J.H. Yang); 박혜선(H.S. Park); 정재훈(J.H. Jung); 송민아(M.A. Song) (Biuletyn Uniejowski, 2011)
Electron beam evaporation source is widely used to prepare thin films by physical vapor deposition because it is very effective to vaporize materials and there is virtually no limit to vaporize materials including metals and compounds such as oxide. In this study, evaporation characteristics of various metals and compounds from an electron beam evaporation source have been studied. The 180 degree deflection type electron beam evaporation source which has 6-hearth crucibles and is capable of inputting power up to 10 kW was employed for evaporation experiment. 36 materials including metals, oxides and fluorides have been tested and described in terms of optimum crucible liner, evaporation state, stability, and so on. Various crucible liners have been tried to find out the most effective way to vaporize materials. Two types of crucible liners have been employed in this experiment. One is contact type liner, and the other is non-contact type one. It has been tried to give the objective information and the most effective evaporation method on the evaporation of materials from the electron beam evaporation source. It is concluded that the electron beam evaporation source can be used to prepare good quality films by choosing the appropriate crucible liner.